2021
DOI: 10.1097/sle.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Laparoscopic Common Bile Duct Exploration in Patients With Previous Failed Endoscopic Retrograde Cholangiopancreatography

Abstract: Background: The aim was to compare the outcomes of laparoscopic common bile duct exploration (LCBDE) after failed endoscopic retrograde cholangiopancreatography (group A) versus primary LCBDE (group B) for the management of gallbladder and common bile duct stones. Materials and Methods:A comprehensive and systematic literature search was performed in several databases, including PubMed, Ovid, and Cochrane Library. Meta-analysis of operative outcomes, postoperative outcomes, and gallstone clearance rates was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(175 reference statements)
0
2
0
Order By: Relevance
“…There was also no significant difference in the postoperative bile duct stricture or reoperation observed. The higher risk of bile leak and early peritonitis after LTDE is the most frequent complication, which can be explained by the fact that bile duct suturing is a challenging task and has a significant learning curve [60]. According to the literature, the operation time of LCBDE decreases as the experience of the surgeon increases (Zhu et al, 2015).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…There was also no significant difference in the postoperative bile duct stricture or reoperation observed. The higher risk of bile leak and early peritonitis after LTDE is the most frequent complication, which can be explained by the fact that bile duct suturing is a challenging task and has a significant learning curve [60]. According to the literature, the operation time of LCBDE decreases as the experience of the surgeon increases (Zhu et al, 2015).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis found that LC and LCBDE after previous ERCP-ES failed CBD clearance had acceptable results and constituted a reliable alternative choice after endoscopic failure[ 43 ]. A recent retrospective study from the United Kingdom found that the transcystic or transductal approach for LCBDE had similar results regarding stone clearance, conversion to open surgery and mortality, but morbidity and complications were higher in the transductal route[ 44 ].…”
Section: Managementmentioning
confidence: 99%